2016
DOI: 10.1099/jmm.0.000315
|View full text |Cite
|
Sign up to set email alerts
|

Class 1 integrons in non-clonal multidrug-resistant Acinetobacter baumannii from Iran, description of the new bla IMP-55 allele in In1243

Abstract: Infections and outbreaks caused by multidrug-resistant Acinetobacter baumannii (MDR-AB) are prevalent and have been reported worldwide over the past 20 or more years. Class 1 integron in MDR-AB plays an important role in the spread of antibiotic resistance in clinical settings. This study has been conducted to evaluate the detection of metallo-b-lactamase, characterization of class 1 integron and determination of clonal relatedness among A. baumannii hospital isolates. Sixty-five clinical isolates of MDR-AB we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 39 publications
1
23
0
1
Order By: Relevance
“…The findings of the current study revealed that all isolates were susceptible to at least one antibiotic, but most isolates were resistant to most antibiotics. Similar to our data, Bassetti and Shakibaie studies showed that different isolates of A. baumannii were resistant to most antibiotics, and 70% of A. baumannii isolates were resistant to 3 or more antibiotics (9,21). According to various reports, the majority of A. baumannii isolated in Iran were resistant against the first-line drugs of Aminoglycosides, Ceftazidime, Fluoroquinolones, Imipenem, Meropenem (22,23).…”
Section: Discussionsupporting
confidence: 89%
“…The findings of the current study revealed that all isolates were susceptible to at least one antibiotic, but most isolates were resistant to most antibiotics. Similar to our data, Bassetti and Shakibaie studies showed that different isolates of A. baumannii were resistant to most antibiotics, and 70% of A. baumannii isolates were resistant to 3 or more antibiotics (9,21). According to various reports, the majority of A. baumannii isolated in Iran were resistant against the first-line drugs of Aminoglycosides, Ceftazidime, Fluoroquinolones, Imipenem, Meropenem (22,23).…”
Section: Discussionsupporting
confidence: 89%
“…A BLAST search with the first 300 nt of the aadB transcript yields hits to Ͼ100 A. baumannii genomes, with coverage ranging from 73% to 100%. Integrons encoding aminoglycoside modifying enzymes, including aadB, are also widely reported in the A. baumannii literature (45)(46)(47)(48)(49)(50). As the ϳ300-nt sRNA appears to be encoded mostly within the integron promoter region, it is possible that other integrons, even those not harboring aadB, still contain this transcript.…”
Section: Discussionmentioning
confidence: 99%
“…Transposons, such as Tn2006, Tn2007, and Tn2008, increase the spread of resistance genes and may present integrons, which were captured and express exogenous resistance genes 40,48,59 . Thus, integrons are composed of gene cassettes, and classes 1 and 2 are commonly found in A. baumannii clinical isolates [60][61][62] . As previously stated, insertion sequences act as strong promoters that increase the resistance levels of OXA carbapenemases in A. baumannii isolates 47,59,63 .…”
Section: Acinetobacter Baumannii Contextmentioning
confidence: 99%